2006
DOI: 10.1073/pnas.0604725103
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Clostridium difficile toxin B cardiotoxicity using a zebrafish embryo model of intoxication

Abstract: Clostridium difficile toxin B (TcdB) has been studied extensively by using cell-free systems and tissue culture, but, like many bacterial toxins, the in vivo targets of TcdB are unknown and have been difficult to elucidate with traditional animal models. In the current study, the transparent Danio rerio (zebrafish) embryo was used as a model for imaging of in vivo TcdB localization and organ-specific damage in real time. At 24 h after treatment, TcdB was found to localize at the pericardial region, and zebrafi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
57
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 54 publications
6
57
0
Order By: Relevance
“…This finding drew into question the long-standing hypothesis that TcdA was actually more important in the pathogenesis of disease, but was in agreement with other recent work highlighting the importance of TcdB. 1,2,7 Our work also confirmed that systemically administered antibodies were detectable not only in the blood, as expected, but were also detectable in the intestinal lumen.…”
Section: Introductionsupporting
confidence: 76%
“…This finding drew into question the long-standing hypothesis that TcdA was actually more important in the pathogenesis of disease, but was in agreement with other recent work highlighting the importance of TcdB. 1,2,7 Our work also confirmed that systemically administered antibodies were detectable not only in the blood, as expected, but were also detectable in the intestinal lumen.…”
Section: Introductionsupporting
confidence: 76%
“…Furthermore, since toxins can induce their own transport to the basolateral/ systemic side ( Fig. 6 and reference 30), perhaps allowing them to enter the circulation and reach other organs (39,40), circulating neutralizing antibodies should prevent systemic effects, if any, of C. difficile toxins. Whether these advantages will translate to systemically administered antibodies, such as actoxumab-bezlotoxumab, versus orally delivered neutralizing antibodies remains to be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…However, systemic toxin is not indicative of a normal infection scenario, since the majority of clinical manifestations of CDAD are selflimiting within the intestine (51). In life-threatening cases, however, systemic complications have been documented (52)(53)(54)(55)(56), and entry of the toxin into circulation is thought to be a possible cause (57). Therefore, challenging immunized mice with intraperitoneal toxin represents a stringent method for assaying the nAb response.…”
Section: Discussionmentioning
confidence: 99%